2008
DOI: 10.7326/0003-4819-149-7-200810070-00006
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factors, Their Binding Proteins, and Prostate Cancer Risk: Analysis of Individual Patient Data from 12 Prospective Studies

Abstract: Background Some, but not all, published results have shown an association between circulating blood levels of some insulin-like growth factors (IGFs) and their binding proteins (IGFBPs) and the subsequent risk for prostate cancer. Purpose To assess the association between levels of IGFs and IGFBPs and the subsequent risk for prostate cancer. Data Sources Studies identified in PubMed, Web of Science, and CancerLit. Study Selection The principal investigators of all studies that published data on circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
103
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(111 citation statements)
references
References 37 publications
6
103
2
Order By: Relevance
“…Serial reports from the Health Professionals Follow‐up Study (HPFS), a large prospective cohort study comprising 51 529 male health professionals from the United States, aged 40‐75 years at enrollment in 1986, demonstrate that circulating IGF‐1 level is positively associated with low‐grade, but not with high‐grade, prostate cancer 10, 11, 12. Associations between serum IGF‐1 level and low‐grade prostate cancer have also been shown by a pooled analysis of 12 prospective studies,13 and the results of other large prospective cohort studies, such as the Physicians’ Health Study (PHS) 14 and the European Prospective Investigation into Cancer and Nutrition (EPIC) study 15. These findings imply that there are stronger effects of IGF‐1 on the development of low‐grade prostate cancer than on the development of high‐grade disease.…”
Section: Introductionmentioning
confidence: 86%
“…Serial reports from the Health Professionals Follow‐up Study (HPFS), a large prospective cohort study comprising 51 529 male health professionals from the United States, aged 40‐75 years at enrollment in 1986, demonstrate that circulating IGF‐1 level is positively associated with low‐grade, but not with high‐grade, prostate cancer 10, 11, 12. Associations between serum IGF‐1 level and low‐grade prostate cancer have also been shown by a pooled analysis of 12 prospective studies,13 and the results of other large prospective cohort studies, such as the Physicians’ Health Study (PHS) 14 and the European Prospective Investigation into Cancer and Nutrition (EPIC) study 15. These findings imply that there are stronger effects of IGF‐1 on the development of low‐grade prostate cancer than on the development of high‐grade disease.…”
Section: Introductionmentioning
confidence: 86%
“…For sex hormones, a pooled analysis of individual participant data from 18 studies found no significant associations 23 , but more data are needed to explore the relationship where both, decreased overall risk 23 and an increased risk of high-grade cancer have been reported 24 . For insulin-like growth factors (IGFs), a pooled analysis of individual participant data from 12 studies showed a significant positive association between circulating IGF-I and prostate cancer risk 25 ; more data are required on IGF-II and IGF binding proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic disturbances also affect this axis, which is itself strongly associated with PCa (Monti et al 2007). Recent prospective epidemiology has consistently shown strong associations between circulating IGF1 levels and the subsequent risk of developing PCa (Roddam et al 2008). The actions of the IGFs are modulated by a family of high-affinity IGF-binding proteins (IGFBPs 1-6) that can either inhibit or enhance the actions of the IGFs.…”
Section: Introductionmentioning
confidence: 99%